Disclosure of cardiac variants of uncertain significance results in an exome cohort. Issue 5 (2nd March 2018) - Lawal, T.A.; Lewis, K.L.; Johnston, J.J.; Heidlebaugh, A.R.; Ng, D.; Gaston‐Johansson, F.G.; Klein, W.M.P.; Biesecker, B.B.; Biesecker, L.G.
Abstract : This study examined the impact of disclosing subclassifications of genetic variants of uncertain significance (VUS) on behavioral intentions. We studied return of VUS results to 79 individuals with a cardiomyopathy‐associated VUS, subclassified into VUS‐high or VUS‐low. Primary outcomes were perceived risk (absolute and comparative), perceived severity, perceived value of information, self‐efficacy, decision regret, and behavioral intentions to share results and change behaviors. There was no significant difference between the 2 subclasses in overall behavioral intentions ( t = 0.023, P = .982) and each of the individual items on the behavioral intentions scale; absolute ( t = −1.138, P = .259) or comparative ( t = −0.463, P = .645) risk perceptions; perceived value of information ( t = 0.582, P = .563) and self‐efficacy ( t = −0.733, P = .466). Decision regret was significantly different ( t = 2.148, P = .035), with VUS‐low (mean = 17.24, SD = 16.08) reporting greater regret. Combining the subclasses, perceived value of information was the strongest predictor of behavioral intentions ( β = 0.524, P < .001). Participants generally understood the meaning of a genetic VUS result classification and reported satisfaction with result disclosure. No differences in behavioral intentions were found, but differences in decision regret suggest participants distinguish subclasses of VUS results. The perceived value of VUS may motivate recipients to pursue health‐related behaviors. Abstract : Disclosure of cardiac variants of uncertain significance results in an exome cohort. HGMD: human gene mutation database; NHLBI ESP: National Heart, Lung, & Blood Institute Exome Sequencing Project; ExAC: Exome Aggregation Consortium; CADD: Combined Annotation Dependent Depletion. Statistical significance set at P < .05.